Temporal variations in bio-indices of Oreochromis niloticus (Linnaeus, 1758) in East Kolkata wetlands, India - Kumar, Avinash; Das, Sudhir Kumar; Bhakta, Dibakar (Journal of the Inland Fisheries Society of India, 2021)
Temporal variations in selected bio-indices of length-weight relationships (LWRs) like relative condition factor (Kn), relative length of gut (RLG), hepato-somatic index (HSI), gonado-somatic index (GnSI) and gastro-somatic index (GaSI) of Nile tilapia (Oreochromis niloticus) were carried out in 341 samples collected at fortnightly intervals in East Kolkata wetlands, a Ramsar site. The exponent b value of LWRs was 2.9869, 2.8316 and 2.9163 with r2 value being 0.938, 0.936 and 0.935 for male, female and the pooled sample respectively showing negative allometric growth of the fish. The Kn values ranged 1.01 to 1.09 and 1.05 to 1.12 for male and female samples respectively exhibiting significant difference (p